Collaborations within Erasmus International Program - Smaranda Moldovan; Ioana Palamar (Journal of Research and Innovation for Sustainable Society)
The article focuses on university collaborations in terms of organising visual art exhibitions and workshops between our universities and other European art institutions within the frame of Erasmus International program